If you give a mouse a cookie - Numeroff, Laura Joffe (HarperCollins Publishers, 1985)
Relating the cycle of requests a a mouse is likely to make after you give him a cookie takes the reader through a young boy's day.
Keywords: Children's stories, American; Mice-Fiction